Pengaruh Kualitas Pelayanan, Harga Kompetitif, Dan Keandalan Teknisi Terhadap Kepuasan Konsumen Car Wash Ansor Di Cinta Makmur Kecamatan Panai Hulu - Ila Mardianti; Yuniman Zebua; Mulya Rafika (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the effect of service quality, competitive pricing, and technician reliability on customer satisfaction at Car Wash Ansor in Cinta Makmur Village, Panai Hulu District. This research employs a quantitative approach with a causal associative design. Primary data were collected through questionnaires distributed to 100 respondents using a census sampling technique. Data were analyzed using multiple linear regression with the assistance of the Statistical Package for the Social Sciences (SPSS). The results show that partially, service quality has a positive and significant effect on customer satisfaction with a t-value of 3.543 and a significance level of 0.001. Competitive pricing has a positive and significant effect with a t-value of 5.121 and a significance level of 0.000, and it is the most dominant variable. Technician reliability also has a positive and significant effect with a t-value of 2.192 and a significance level of 0.031. Simultaneously, service quality, competitive pricing, and technician reliability significantly affect customer satisfaction with an F-value of 15.210 and a significance level of 0.000. The coefficient of determination (R²) of 0.322 indicates that these variables explain 32.2% of the variation in customer satisfaction.